A commentary about The transfigured reality of Luis Villoro (Devenires, 2011)
In the article that opens this issue of becomings, master Luis Villoro addresses an important aspect of the novel by Miguel de Cervantes: the relationship between reality and poetic creation. I hope not to distort its central idea if I condenso thus: the reality imagined by the novel —or poetry— is a transfigured reality manifests itself by the excitement and enthusiasm that pointing out what it is called reality is a delusion, beat beating this and creating a higher reality imagined. I suggest that some of the reasons why don Quixote in a maker of new realities from the reality that manages transfigurar, based on book, Reading and the new literary genre Announces. Don Quixote is a multitude of books and a book in which the reference to the books is constant. And there are no books without readers, is worth mentioning the fact that social differences no implied a different culture; cultural elites paid attention to the rich oral literature and illiterates were not excluded know most popular literary works of the time by reading out loud made of them.